Function and Importance of Self-Access Learning Centers (SALC) in the University of Veracruz. - Sánchez Hernández, Diana Iveth (Universidad Pedagógica y Tecnológica de Colombia, 2024)
This article presents a review of the current literature and official websites to explain the use, function, and importance of the self-access centers (CAA) of the Universidad Veracruzana (University of Veracruz). The article covers how these centers were first conceived, how they function, as well as the present situation of the self-access center of the School of Languages of the university, where I have had the opportunity to collaborate and observe how it is managed. I also analyze the role of the teacher-advisor as an advocate of autonomous learning who provides guidance so that the students become self-sufficient learners who can develop their own learning skills independently. Finally, I analyze the different perspectives that can be observed in the research work on self-access centers carried out in Mexico and the University of Veracruz, among which the themes related to efficacy and the shortcomings of self-access centers are addressed.